DAYA HAMBAT EKSTRAK BUAH ANDALIMAN (Zanthoxylum acanthopodium DC) DALAM ETIL ASETAT TERHADAP PERTUMBUHAN Escherichia coli - Sitanggang, Fitri Maria Clarensia; Duniaji, Agus Selamet; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
This study aims to determine the Minimum Inhibitory Consentration (MIC) of andaliman fruit extract ( Zanthoxylum acanthopodium DC) in ethyl acetate against the growth of Escherichia coli bacteria. The design of this study used an experimental method with 10 extract concentrations for MIC testing, namely 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% with 2 repetitions so that they were obtained 20 experimental units. The variables observed were the formation of clear zones, namely the inhibition produced by the presence of antimicrobial activity from andaliman fruit extract in ethyl acetate against the growth of Escherichia coli . Data from research results are presented in the form of tables, figure and discussed descriptively. Andaliman fruit extracts in ethyl acetate have varying inhibitory forces, namely at the concentrations of concentrations of 10% to 20% was 0.65 mm to 3.15 mm with weak inhibition categories, concentrations of 30% to 50% was 5.25 mm to 6, 60 mm in the moderate inhibition category and concentrations of 60% to 100% showed strong inhibition categories with inhibition diameters of 7.20 mm to 9.60 mm. Minimum Inhibitory Concentration (MIC) for the growth of Escherichia coli was at the concentration of 60% with a clear zone diameter of 7.2 mm with a strong category.     Keywords : Andaliman fruit, Escherichia coli, antibacterial.